Per uno studio sulla procedura delle concordanze (ENTHYMEMA, 2012)
The procedure of concurrences designates an interpretative technique only apparently generating from the most guarded Structuralism: even before being a method of study, as a matter of fact it represents a possibility of the text, from the point of view of the reader, of the critic, and of the author. In this article we are analyzing concurrences firstly through the experiences of three philologists of the last century (Barbi, Contini and Avalle), in order to provide a technical examination, by referring to a specific category brought back up by Franco Brioschi (exemplification).